Breastfeeding practices based on the gestational age and weight at birth in the first six months of life in a population-based cohort of infants from North India - Sharma, Sitanshi; Chowdhury, Ranadip; Taneja, Sunita; Mazumder, Sarmila; Bhatia, Kiran; Ghosh, Runa; Karantha, Sowmya C.; Dhabhai, Neeta; Chellani, Harish; Bahl, Rajiv; Bhandari, Nita (Frontiers in Pediatrics, 2023)
Background Short and long term benefits of early initiation of breastfeeding (EIBF) and exclusive breastfeeding (EBF) in first 6 months of life are indisputable. Reliable estimates of breastfeeding practices as per gestational age and weight at birth are not available from low and middle income countries. Objective To assess the impact of breastfeeding counselling on EIBF and EBF during first 6 months of life according to gestational age and weight at birth. Methods We analysed data from, Women and Infants Integrated Interventions for Growth Study (WINGS). Mothers were counselled on EIBF during third trimester of pregnancy and supported during infant’s first 6 months to continue EBF by frequent home visits. Breastfeeding practices were ascertained through 24 hour recall at infant ages 1, 3 and 5 months for both intervention and control groups by an independent outcome ascertainment team. World Health Organization (WHO) definitions were used for classification of infant breastfeeding practices. Generalized linear models of Poisson family with log-link function were used to estimate effect of interventions on breastfeeding practices. Relative measures of effect on breastfeeding practices were estimated in, term appropriate for gestational age (T-AGA), term small for gestational age (T-SGA), preterm AGA (PT-AGA), preterm SGA (PT-SGA) infants. Results EIBF was (51.7%) higher in intervention group (IRR 1.38, 95% CI 1.28-1.48) compared to control group. Proportion of infants with EBF at ages 1 month (IRR 1.37, 95% CI 1.28-1.48), 3 months (IRR 2.13, 95% CI 1.30-1.44) and 5 months (IRR 2.78, 95% CI 2.58-3.00) were higher in intervention group. There was significant interaction (p value for interaction <0.05) between interventions and gestational age and weight at birth on EBF in PT-SGA infants at 3 months (IRR 3.30, 95% CI 2.20-4.96) and at 5 months of age (IRR 5.26, 95% CI 2.98-9.28). Conclusion This is the first study wherein impact of breastfeeding counselling in first 6 months of life was assessed according to reliably estimated gestational age and weight at birth. Effect of interventions was higher in preterm and SGA infants compared to other infants. Intensive breastfeeding counselling is likely to improve breastfeeding rates and reduce adverse health outcomes.